EFEKTIFITAS PELAKSANAAN TRANSAKSI EFEK MELALUI SCRIPLESS TRADING DI PASAR MODAL INDONESIA - Faisal, Navila; Supasti Darmawan, Ni Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
In order to perform national development, particularly in order to aim the development goals, it is needed any supporting facilities such as a law order which supports, moves and controls many development activities in economy field. Scripless Trading term can be said as a trading without a stock letter or it can also named as a trading without any securities letters The existence of scioless trading in capital market can indicate how that advanced scripless securities trading system can be applied by law, particularly in capital market law, so it can give out benefits as much as it possible in law field, law products or its impact on law progress as securities which is traded in capital market.
Keywords: Review, Script Less Trading, Securities Transaction Implementation